Non-exchangeable hydrogen (δ2H) stable isotope ratios in fauna provide enhanced dietary, isotopic niche and home range reconstruction at Aqaba Castle, Jordan - Gene T. Shev; Bea De Cupere; Anastasia Brozou; Benjamin T. Fuller; Marcello A. Mannino; Joris Peters; Wim Van Neer; Steven Bouillon; Claudio Ottoni (PLoS ONE, 2025)
Bone collagen of terrestrial and marine animals (n = 218) recovered from Ottoman period contexts at Aqaba Castle, Jordan (16th–19th centuries CE), were analyzed for δ13C, δ15N, and δ2H isotope ratios. While δ13C and δ15N values showed considerable overlap among species in the hyperarid environment, δ2H values exhibited less overlap, enhancing stable isotopic niche differentiation. In domesticates, δ2H values show trophic enrichments of +18.4‰ from herbivores to omnivores (dogs), and +26‰ to cats which had the highest δ2H values. Fish δ2H values show a positive relationship with increasing trophic level but also moderately correlate with body size (r = 0.61, R2 = 0.37). The offset between collagen δ2H and rainfall (δ2Hmw) values is smaller for camels (−1.4‰), sheep (−4.5‰), and goats (+6.8%), than for chickens (−18.5‰) and cattle (−27.0‰) due to more frequent consumption of 2H-depleted groundwater by the latter species, because of their higher water requirements. Similarities between local precipitation and bone collagen δ2H values for most terrestrial herbivores suggest the utility of δ2H values for geographic provenancing. This is explored by overlapping gazelle and chukar collagen δ2H values over a regional δ2Hmw isoscape, tentatively suggesting these species inhabited the water-stressed highland environments surrounding Aqaba Castle. This study demonstrates the advantages of incorporating bone collagen δ2H values alongside δ13C and δ15N values as a useful environmental proxy, enhancing interpretations of animal dietary behaviour, trophic levels, water sources, and wild animal home ranges.